Genome-based identification of the CYP75 gene family in Orchidaceae and its expression patterns in Cymbidium goeringii - Li, Yuanyuan; Zhao, Xuewei; Zhang, Meng-Meng; He, Xin; Huang, Ye; Ahmad, Sagheer; Liu, Zhong-Jian; Lan, Siren (Frontiers in Plant Science, 2023)
With a great diversity of species, Orchidaceae stands out as an essential component of plant biodiversity, making it a primary resource for studying angiosperms evolution and genomics. This study focuses on 13 published orchid genomes to identify and analyze the CYP75 gene family belonging to the cytochrome P450 superfamily, which is closely related to flavonoid biosynthetic enzymes and pigment regulation.We found 72 CYP75s in the 13 orchid genomes and further classified them into two classes: CYP75A and CYP75B subfamily, the former synthesizes blue anthocyanins, while the latter is involved in the production of red anthocyanins. Furthermore, the amount of CYP75Bs (53 / 72) greatly exceeds the amount of CYP75As (19 / 72) in orchids. Our findings suggest that CYP75B genes have a more important evolutionary role, as red plants are more common in nature than blue plants. We also discovered unique conserved motifs in each subfamily that serve as specific recognition features (motif 19 belong to CYP75A; motif 17 belong to CYP75B). Two diverse-colored varieties of C. goeringii were selected for qRT-PCR experiments. The expression of CgCYP75B1 was significantly higher in the purple-red variant compared to the yellow-green variant, while CgCYP75A1 showed no significant difference. Based on transcriptomic expression analysis, CYP75Bs are more highly expressed than CYP75As in floral organs, especially in colorful petals and lips. These results provide valuable information for future studies on CYP75s in orchids and other angiosperms.